2010
DOI: 10.2355/isijinternational.50.491
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Compressible Flow Simulation of Top-blown Multiple Jets in Converter

Abstract: A three-dimensional mathematical model has been developed to simulate the compressible jets flow from the top-blown lance with multi-nozzles in converter to a free surrounding domain. The variations of fluid density and viscosity, high temperature, and Mach number were taken into consideration in this model which was validated against the physical modeling results. More specifically, computations were obtained to compare the widely used realizable k-e turbulence model against the standard k-w turbulence model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 13 publications
(28 reference statements)
3
44
0
Order By: Relevance
“…one equation turbulence models, 32,34) two-equation turbulence models. 44,[96][97][98][99] In this way, the converter steelmaking can be expressed in terms of some physical variables using partial differential equations with appropriate operating and boundary equations. Subsequently, it is the generation of grid in the domain and discretization of the established partial differential equations into algebraic form using different schemes.…”
Section: Construction Of the Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…one equation turbulence models, 32,34) two-equation turbulence models. 44,[96][97][98][99] In this way, the converter steelmaking can be expressed in terms of some physical variables using partial differential equations with appropriate operating and boundary equations. Subsequently, it is the generation of grid in the domain and discretization of the established partial differential equations into algebraic form using different schemes.…”
Section: Construction Of the Mathematical Modelmentioning
confidence: 99%
“…Figure 4 shows some modeling results regarding to the supersonic jets. 40,44) These studies explored the fundamental behavior of the supersonic jets and greatly helped in propagating the knowledge on oxygen lance performance and its design. R. Sambasivam et al 132) designed a new oxygen lance with a central subsonic nozzle as described in Fig.…”
Section: Supersonic Oxygen Flow Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the coalescence of the jets reduced the impact of the individual jets and that CFD is a useful design tool when considering different operations of the LD converter. [23] Li et al also modeled the coalescence of multiple jets in the BOF process. Like Wang, Li chose the k-v turbulence model, and found that the ambient temperature has a great influence on the jet coalescence.…”
Section: Reviewmentioning
confidence: 99%
“…Odenthal [44] 2010 AOD 3D Transient Realizable k-e/ SST-SAS Side blowing, oscillations Wang [23] 2010…”
Section: Top Blowingmentioning
confidence: 99%